Job Satisfaction as a Mediator Between Work Conflict and Employee Performance - Lewaherilla, Novalien Carolina (ADMAN: Journal of Contemporary Administration and Management, 2025)
This study examines the influence of work conflict on employee performance, with job satisfaction as a mediating variable at PT. Mutiara Bakery Ambon. The objective of this research is to test and analyze whether job satisfaction mediates the relationship between work conflict and employee performance. The population consists of 35 employees, and a saturated sampling technique was employed. The analytical tool used in this research is SmartPLS 3.0 with Structural Equation Modeling (SEM) as the analysis method. The results show that work conflict has no significant effect on employee performance, and it also does not significantly affect job satisfaction. However, job satisfaction has a positive and significant effect on employee performance. Furthermore, job satisfaction is proven to mediate the effect of work conflict on employee performance.